LGBT, Religion, and Human Rights: a Study on Khaled M. Abou El-Fadl’s Thoughts - Sa'dan, Masthuriyah (Jurnal Perempuan, 2015)
The Fatwa ”Haram” of MUI against homosexual orientation (LGBT) and the death penalty against LGBT had shaken the Indonesian, and further marginalized ”third” gender people. ”Religion” is urged to provide justice to the Ummah but the Ulema did the opposite thing by discriminating sexual minorities. The legal instrument of regional, national and international human rights has recognizes LGBT rights as basic human rights. Islamic religion in this case Shari’ah and Islamic law is used as a theological foundation by MUI to issued the fatwa that is contrary to the concept of human rights. The progressive interpretation of Khaled M. Abou El-Fadl became important to be studied to protect LGBT. Khaled attempted to break up the tension between religion (Islam) and human rights by using the social approach of contemporary humanities. By this means, Abou El-Fadl introduced a scheme of protection to LGBT under Quranic Syariah Law.